ANALISIS PEMBIAYAAN PADA BANK UMUM NASIONAL KONVENSIONAL DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Nisadela Amanda, - (2019)
This research is using quantitative study aimed to see wheter there is analysis of financing on conventional national commercial bank with profitability as intervening variable which recorded in Financial Services Authorit. Dependent variables in this research is Financing and Profitability as intervening variable. While the independent variable are Inflation and Exchange Rate. The population in this study are all national commercial banks in Indonesia, amounting to 64 banks. Sampel selection is done by using purposive sampling. The data used in this research is secondary data and methods of analysis is regression panel data using E-views program. The sample used in this study as many as 32 Conventional National Commercial Bank in Indonesia 2015-2017. The result of the testing panel data regression analysis using a significant level of 0.05 indicates that the inflation has significant effect on financing through probitability, exchange rate has no significant effect on financing through probitability, inflation has no significant effect on financing, and exchange rate has no significant effect on financing.